Incorporating Resilience Factors Into the Interpersonal Theory of Suicide: The Role of Hope and Self‐Forgiveness in an Older Adult Sample. Issue 1 (8th October 2015) - Cheavens, Jennifer S.; Cukrowicz, Kelly C.; Hansen, Ryan; Mitchell, Sean M.
Abstract : Objectives: The interpersonal theory of suicide posits that perceived burdensomeness and thwarted belongingness are risk factors for suicide ideation. To more comprehensively characterize this model, it is important to identify resilience factors. Forgiveness of oneself may attenuate the relation between perceived burdensomeness and suicide ideation. Similarly, hope might weaken the association between thwarted belongingness and suicide ideation. Method: We examined these relations cross‐sectionally in a sample ( N = 91) of older adults after including symptoms of depression and demographic variables in the models. Results: Self‐forgiveness moderated the relation between perceived burdensomeness and suicide ideation. Hope did not moderate the relation between thwarted belongingness and suicide ideation. Conclusions: These findings suggest that including resilience factors (i.e., self‐forgiveness) in models of suicide ideation may result in better identification of those most at risk for suicide and may allow for more precise intervention targets.